Persepsi Siswa Terhadap Keterampilan Mengajar Mahasiswa Praktik Pengalaman Lapangan pada Jurusan Teknik Instalasi Tenaga Listrik - Rossa Indah; Aswardi Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to see how students perceive the teaching skills of Praktik Pengalam Lapangan (PPL) students at the Jurusan Teknik Instalasi Tenaga Listrik at SMK Negeri 5 Padang. The method used in this research is descriptive with a quantitative approach. The data analysis technique was carried out by counting the number of respondents' answers to each statement item. The population of this study were all students who took the subject of Pekerjaan Dasar Elektromekanik at the Jurusan Teknik Instalasi Tenaga Listrik at SMK Negeri 5 Padang as many as 105 people. The sample of this study was obtained as many as 51 people using the Systematic Random Sampling technique. Based on the research instrument test, the validity of 32 statement items was obtained with a reliability test of 0.883. The results of the study stated that students' perceptions of the teaching skills of Praktik Pengalam Lapangan (PPL) students at the Jurusan Teknik Instalasi Tenaga Listrik at SMK Negeri 5 Padang were categorized as good with a percentage of 78.4%, which consisted of (1) asking skills 64.7%, (2) skills giving reinforcement 62.7%, ( 3) explaining skills 70.6%, (4) teaching variation skills 53%, (5) skills guiding small group discussions 58.8%, (6) opening and closing lessons 50.9% which is stated in good category and (7) processing skills 43.1% class, (8) small group and individual teaching skills 49.1% are categorized as quite good. So the overall perception of students towards teaching skills of Praktik Pengalam Lapangan (PPL) students at the Jurusan Teknik Instalasi Tenaga Listrik at SMK Negeri 5 Padang has been carried out well.